Assessment of the use of dynamic mechanical analysis to investigate initial onset of brown rot decay of Scots pine (Pinus sylvestris L.). (May 2017) - Ormondroyd, G.A.; Alfredsen, G.; Prabhakaran, R.T. Durai; Curling, S.F.; Stefanowski, B.K.; Spear, M.J.; Gobakken, L.R.
Abstract: Microbiological degradation of wood by decay fungi can cause a rapid change in the structural properties of timber which can result in both strength and mass loss. Traditional techniques for the evaluation of decay (e.g. mass loss) lack the sensitivity to evaluate the effects of the very first stages of the decay process. This paper describes the effects of initial brown rot decay, defined by the amount of Poria placenta genomic DNA (gDNA) present in the samples, on the dynamic mechanical properties of the timber. It was found that there is a correlation between the mean storage modulus of the timber and the amount of P. placenta gDNA present, and therefore the level of decay. This shows that using dynamic mechanical analysis is a viable technique that can be used to study initial decay processes. Highlights: Initial Poria placenta decay was assessed between 0 and 17 days exposure. Samples were assessed for the presence of fungi through gDNA analysis and for changes in mechanical properties via DMTA. There was good correlation between the amount of gDNA and the changes in the mean storage modulus.